EFEKTIVITAS MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWADI SMAN 10 PONTIANAK - Fitri, Rafika; Imran, Imran; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effectiveness of problem based learning model to increase the students’ learning outcomes in the Civic Education Subject. This is an experimental study on the 10th-grade Social 3 Students of SMA Negeri 10 Pontianak. This study was conducted in the form of pre-experimental with one-group pretest-posttest design. 32 students participated in the study. The research instruments used are 15 multiple-choice test items for the pretest and 15 for the posttest. The average scores collected from the pretest and posttest are 78,81 and 93. Accordingly, it indicates that there is a difference in the results of students’ learning outcomes; therefore, Ho is rejected and Ha is accepted. With the effect size by 1,57 (high category), it is concluded that the applied learning model highly improved the students’ learning outcomes in the Civic Education subject at Grade 10 Social 3 SMA Negeri 10 Pontianak, especially on the material discussing Threat to the state in the frame of Bhinneka Tunggal Ika.Keywords: Effectiveness, Learning Model, Problem Based Learning, Learning Outcomes